Film Viewers' Motives and Satisfaction are Somewhere Laen (Uses and Gratification Analysis of the Palmgreen Model on Members of Imami UIN-Suka Yogyakarta) - Luthfi, Hamzah; Andryani, Kristina; Saputri, Dhea Octavia (PT FORMOSA CENDEKIA GLOBAL, 2025)
The film